2013
DOI: 10.1002/qj.2106
|View full text |Cite
|
Sign up to set email alerts
|

Operational assimilation of ozone‐sensitive infrared radiances at ECMWF

Abstract: ECMWF has been assimilating ozone-sensitive infrared (IR/O 3 ) radiances from AIRS, IASI, and HIRS in its operational system since November 2011. We present a detailed assessment of the value of assimilating these observations, as well as the steps that have been taken to successfully merge the infrared information with that provided by ozone products retrieved from UV sensors. In general, the assimilation of the IR/O 3 radiances improves the agreement between the ozone analyses and independent ozone data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…This is particularly the case for the assimilation of TCO 3 . An example of a background error profile and vertical correlation matrix obtained from Dragani and McNally (2013) is given in Fig. 3.…”
Section: The Data Assimilation Systemmentioning
confidence: 99%
“…This is particularly the case for the assimilation of TCO 3 . An example of a background error profile and vertical correlation matrix obtained from Dragani and McNally (2013) is given in Fig. 3.…”
Section: The Data Assimilation Systemmentioning
confidence: 99%
“…It is unclear at this point whether tracer observations from current satellites are of sufficient accuracy and frequency to benefit wind analyses in an operational setting; a potential source of operational ozone profiles is the OMPS on the NASA Suomi National Polar-orbiting Partnership (NPP) mission (Flynn et al, 2009), launched 28 October 2011. In addition, ozone-sensitive infrared radiances can potentially provide dynamical information via tracer-wind coupling in NWP systems (Dragani and McNally, 2013). In this study we will examine some of the limitations of wind extraction from ozone assimilation.…”
Section: R Allen Et Al: Limitations Of Wind Extraction From 4d-vmentioning
confidence: 99%
“…Peubey and McNally (2009) isolated the mechanisms whereby geostationary clear-sky radiances can impact the wind analyses in 4D-Var and showed that the dominant factor involves adjustment of the wind field to match observed humidity features (the so-called "tracer advection effect"). However, attempts to assimilate stratospheric ozone using 4D-Var algorithms and the resultant dynamical coupling have previously resulted in problems in operational numerical weather prediction (NWP) (Han and McNally, 2010;Dragani and McNally, 2013). These assimilation challenges led Allen et al (2014) to re-examine the stratospheric tracer-wind problem at a more fundamental level using 4D-Var assimilation studies with a shallow water model (SWM) coupled to the tracer continuity equation.…”
Section: Introductionmentioning
confidence: 99%